Penguatan Kompetensi Metodologi Kuantitatif Statistik Melalui Kegiatan Pelatihan Penulisan Penelitian - Izharul Haq Lamada; Fakhruddin Kurnia M; Puspita Utari; Kurniawan; Ahmad Qadafi (Universitas Ichsan Sidenreng Rappang, 2025)
The purpose of this training program on writing quantitative statistical research methods was to improve students' comprehension and proficiency in accurately applying quantitative research methodology. The curriculum tackles typical problems that students encounter, especially when it comes to creating research frameworks, handling statistical data, and rationally organizing the methodology section. Students from a variety of disciplines who were getting ready for or carrying out academic research participated in the training, which was held at the Pangkajene Regional Library in Sidenreng Rappang Regency. The training offered useful insights into creating variables, sampling strategies, basic statistical data processing, and choosing suitable analysis methods through an interdisciplinary approach. The results demonstrated that participants were better able to create more methodical and empirically supported research methodologies. It is anticipated that this training will play a major role in building a robust and welcoming research culture in higher education.